Geographic distribution and characteristics of genotype A hepatitis B virus infection in acute and chronic hepatitis B patients in Japan. Issue 1 (January 2016) - Ito, Kiyoaki; Yotsuyanagi, Hiroshi; Sugiyama, Masaya; Yatsuhashi, Hiroshi; Karino, Yoshiyasu; Takikawa, Yasuhiro; Saito, Takafumi; Arase, Yasuji; Imazeki, Fumio; Kurosaki, Masayuki; Umemura, Takeji; Ichida, Takafumi; et al.
Abstract: Background and Aims: The prevalence of sexually transmitted acute infections of the genotype A hepatitis B virus (HBV) has been increasing in Japan. Genotype A HBV is associated with an increased risk of HBV progression to chronic infection after acute hepatitis B (AHB) in adults. A nationwide survey was conducted to evaluate the geographic distribution, clinical, and virologic characteristics of genotype A AHB and chronic hepatitis B (CHB) in Japan. Methods: Five hundred seventy AHB patients were recruited between 2005 and 2010, and 3682 CHB patients were recruited between 2010 and 2011. HBV genotypes were determined for 552 and 3619 AHB and CHB patients, respectively. Clinical characteristics were compared among different genotypes in AHB and CHB patients. Genomic characteristics of HBV genotype A were examined by molecular evolutionary analysis. Results: Hepatitis B virus genotype A was the predominant genotype for AHB between 2005 and 2010. Phylogenetic analysis showed that all strains in the AHB patients with genotype A were classified into subtype Ae. Among CHB patients, the occurrence of genotype A was 4.1%, and genotype A was spreading in young adults. In genotype A CHB patients, early stage liver diseases were predominant, although liver diseases progressed to cirrhosis or hepatocellular carcinoma in some patients. Conclusions: The distribution of HBV genotypes is quite different between AHB and CHB in Japanese patients. Genotype A infection is spreading in young adults of Japanese CHB patients. Sequences derived from Japanese AHB patients were identical to or closely resembled the sequences derived from other Japanese AHB patients.